2022
DOI: 10.3390/gels8100652
|View full text |Cite
|
Sign up to set email alerts
|

Designing Deferoxamine-Loaded Flaxseed Gum and Carrageenan-Based Controlled Release Biocomposite Hydrogel Films for Wound Healing

Abstract: In this study, biocomposite hydrogel films made from flaxseed gum (FSG)/kappa carrageenan (CGN) were fabricated, using potassium chloride as a crosslinker and glycerol as a plasticizer. The composite films were loaded with deferoxamine (DFX), an iron chelator that promotes neovascularization and angiogenesis for the healing of wounds. The properties of the biocomposite hydrogel films, including swelling, solubility, water vapor transmission rate, tensile strength, elongation at break, and Young’s modulus studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…The published WVTR data of some commercially available dressings vary from 792 to 4992 g/m 2 /d 1 . Our hydrogel falls within the optimum WVTR range and therefore is more suitable for wound dressing and better than reported other hydrogel films. , …”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…The published WVTR data of some commercially available dressings vary from 792 to 4992 g/m 2 /d 1 . Our hydrogel falls within the optimum WVTR range and therefore is more suitable for wound dressing and better than reported other hydrogel films. , …”
Section: Resultsmentioning
confidence: 59%
“…Our hydrogel falls within the optimum WVTR range and therefore is more suitable for wound dressing and better than reported other hydrogel films. 59,60 Blood Clotting and Hemolysis Profile of Hydrogel Film. A dynamic whole blood clotting model was used to study the in vitro hemostatic property of the hydrogel film shown in Figure 7A.…”
Section: ■ Results and Discussionmentioning
confidence: 99%